2016
DOI: 10.1002/pat.3868
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and properties of fiber reinforced composites using silicon-containing hybrid polymers

Abstract: A novel glass fiber reinforced composite was prepared by using silicon‐containing hybrid polymers, poly(methylhydrogen‐diethynylsilyene) (PMES) and poly(phenylethynyl‐silyloxide‐phenylborane) (APABS), as matrix resins. The curing behavior and rheological properties of the matrix resins were investigated by differential scanning calorimetry (DSC) and rotational rheometer. The dynamic viscoelastic properties, mechanical properties, and microstructures of the composites were studied by dynamic mechanical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For GFRP-M/0.0 (Figure 5(a)), a lot of matrix/fibres were exposed and pulled out, leaving large holes in the fracture surfaces. However, it could be observed that the fracture surfaces of GFRP-M/2.5 (Figure 5(b)) showed a few exposed fibres and the matrix firmly adhere to the surface of fibres, indicating that the interfacial bonding interactions between the fibres and the matrix were strong and very stable [20]. Although there were some fibres exposed for the fracture surfaces of GFRP-M/5.0 (Figure 5(c)), the fibres still remain embedded in the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…For GFRP-M/0.0 (Figure 5(a)), a lot of matrix/fibres were exposed and pulled out, leaving large holes in the fracture surfaces. However, it could be observed that the fracture surfaces of GFRP-M/2.5 (Figure 5(b)) showed a few exposed fibres and the matrix firmly adhere to the surface of fibres, indicating that the interfacial bonding interactions between the fibres and the matrix were strong and very stable [20]. Although there were some fibres exposed for the fracture surfaces of GFRP-M/5.0 (Figure 5(c)), the fibres still remain embedded in the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Various kinds of silicon-containing polymers with reactive C C or Si H linkages have been reported as functional materials, which show excellent high temperature resistance, processability, mechanical, and optical properties as a result of their highly crosslinked network structures formed during thermal curing reaction. [6][7][8][9] Guo et al 10 investigated the thermal curing and degradation behavior of silicon-containing aryacetylene (PSAS) with different substituents (such as Si H and Si CH CH 2 ). They found that the crosslinked structures of PSAS mainly contained phenyl rings and aromatic fused rings, which formed from cyclotrimerization and Diels-Alder reaction of C C and Si C C. Kolel-Veetil et al 11 synthesized a novel kind of poly(carborane-siloxane-arylacetylene) (PCSAA), namely m-PCSAA and p-PCSAA by the reaction of the dimagnesium salts of m-diethynylbenzene or p-diethynylbenzene with 1,7-bis(chlorotetramethyldisiloxyl)-mcarborane.…”
Section: Introductionmentioning
confidence: 99%
“…Novel silicon‐based organic hybrid polymers have attracted intensive and varied interest due to their widely applications in the areas of ceramic precursors, optical materials, solar cells, conducting materials, composite materials, and so forth . Various kinds of silicon‐containing polymers with reactive CC or SiH linkages have been reported as functional materials, which show excellent high temperature resistance, processability, mechanical, and optical properties as a result of their highly crosslinked network structures formed during thermal curing reaction . Guo et al .…”
Section: Introductionmentioning
confidence: 99%